PENGARUH CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL, DAN FREE CASH FLOW TERHADAP DINAMIS PERFORMANCE PERUSAHAAN - Puti Azzahra Vania Eriany (2022)
This study is a quantitative study which aims to empirically examine the effect of corporate governance, intellectual capital, and free cash flow on the dynamic performance of the company. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2020 period. Based on the purposive sampling technique used, it was found that the total research sample was 76 observations from 19 companies that met the sample selection criteria. The analytical method used in testing the hypothesis is multiple linear regression analysis with the help of SPSS software. The results of the study prove that (1) foreign ownership has a positive influence on the dynamic performance of the company. (2) the size of the board of commissioners has no effect on the dynamic performance of the company, (3) intellectual capital has a positive influence on the dynamic performance of the company, (4) free cash flow has no effect on the dynamic performance of the company. Keywords : Company's Dynamic Performance, Foreign Ownership, Size of the Board of Commissioners, Intellectual Capital, Free Cash Flow.